PENGARUH SERVICE QUALITY, DIGITAL MARKETING DAN E-COMMERCE TERHADAP REPEAT PURCHASE DENGAN E-TRUST SEBAGAI VARIABEL INTERVENING PADA ROTI BRILYAN BAKERY DI KABUPATEN SITUBONDO - Moh. Taufiqurrahman; Mohammad Yahya Arief; Yudha Praja (Fakultas Ekonomi dan Bisnis, 2025)
The purpose of this study is to determine the Influence of Service Quality, Digital Marketing and E-commerce on Repeat Purchase with E-Trust as an Intervening Variable at Brilyan Bakery Bread in Situbondo Regency. The sampling technique used in this study was simple random sampling of 98 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the study showed that Service quality had a significant positive effect on E-trust, Digital marketing had a significant positive effect on E-trust, E-commerce had a significant positive effect on E-trust, Service quality had a significant positive effect on Repeat purchase, Digital marketing had a significant negative effect on Repeat purchase, E-commerce had a positive but not significant effect on E-trust, E-trust had a significant positive effect on Repeat purchase, Service quality had a significant positive effect on Repeat purchase through E-trust, Digital marketing had a significant positive effect on Repeat purchase through E-trust, E-commerce had a significant positive effect on Repeat purchase through E-trust.